In the zone - Yu, Bill (Get in the game (Magic Wagon (Firm)), 2021)
Peabody's star pitcher Tony Andia loses his temper when he thinks a player from another team showed him disrespect. His coach asks him to explore whether or not it was a misunderstanding because the player was from a different culture.